Community perceptions of the contributions of parks to sustainability in Canada. Issue 3 (3rd July 2017) - Parker, Pete; Rollins, Rick; Murray, Grant; Chafey, Adam; Cannessa, Rosaline
ABSTRACT: National Parks are thought to contribute to sustainability by addressing conservation, social values and local tourism economies. However, some studies challenge these claims, suggesting that parks can create inequitable flows of costs and benefits to local communities. This study focussed on Pacific Rim National Park Reserve, and five nearby communities. Focus groups and 262 random surveys were used to examine perceived benefits and costs of the park to sustainability. The most important perceived benefits were environmental, followed by economic benefits and social benefits. Perceived costs were rated lower, and were most evident regarding economic impacts (e.g. inflated prices, inflated property values). However, perceptions varied substantially by community, particularly with the First Nations village of Esowista where perceived concerns were greater than in other communities. Contrary to expectations, perceptions were less correlated to length of residence, employment in tourism, employment in the park, involvement in park management or income.